HUBUNGAN POLA MAKAN DENGAN KEJADIAN STUNTING PADA BALITA USIA 12-59 BULAN DI KELURAHAN MATA AIR KOTA PADANG - Meta Rikandi; Ananda Rusman, Denti (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
Stunting is a condition in which toddlers have less length or height when compared to children of their age. The purpose of this study was to determine the relationship between diet and stunting in toddlers aged 12-59 months at Posyandu Kasih Ibu 2, Mata Air Village. This type of research is descriptive analytic using a cross-sectional approach which was carried out at Posyandu Kasih Ibu 2 working areas of the Rawang Barat Health Center in July-August 2023. The study population was 37 people. This study used a questionnaire using the Total Sampling technique. Data analysis used univariate and bivariate data analysis. The results showed that most of the respondents with the highest incidence of stunting were in the normal category of 23 (62.2%) children and the highest eating pattern was in the inappropriate category of 26 (70.3%) of toddlers with the result (p-value = 0.027). It is hoped that the community, especially mothers who have toddlers, must pay attention to fulfilling nutrition by determining the type of food, the amount of food and the frequency of eating according to the needs of children according to their age in providing the right diet so that the incidence of stunting in toddlers is reduced.